MAOA uVNTR Polymorphism Influence on Older Adults Diagnosed with Diabetes Mellitus/Systemic Arterial Hypertension - Gabriel Moura Alves Seixas; Renata de Souza Freitas; Caroline Ferreira Fratelli; Calliandra Maria de Souza Silva; Luciano Ramos de Lima; Marina Morato Stival; Silvana Schwerz Funghetto; Izabel Cristina Rodrigues da Silva (Journal of Aging Research, 2023)
Background. Monoamine oxidase (MAO) is involved in several biological processes associated with well-being and mental health, and alterations in its function might directly impact various mental disorders. Some mental disorders concomitantly occur in individuals with clinical characteristics, such as substance abuse and diabetes. Objective. To analyze the functional MAOA uVNTR polymorphism genotype frequency in an older adult population with diabetes mellitus/arterial hypertension and associate this frequency with clinical characteristics impacting daily life. Methodology. Older adults diagnosed with diabetes mellitus, systemic arterial hypertension, or both (DM/SAH) were selected and had their MAOA gene genotyped for uVNTR polymorphism. The revised Beck Depression Inventory (BDI) and a questionnaire were also applied to determine their mental health and clinical characteristics. Results. The allelic variants detected among the participants were the 2R, 3R, 4R, and 3R/4R heterozygous genotypes. Genotypes solely containing the 3R allele had patients who marked yes for smoking and alcoholism, and only those with the 3R genotypes (female 3R/3R homozygote or male 3R∗ hemizygote) were significant. Although not statistically significant, only 3R and 3R/4R genotypes presented cases of severe depression per the revised BDI interpretations. Conclusion. The MAOA uVNTR polymorphism’s low-activity 3R allele presence in an older adult population diagnosed with DM/SAH may represent a risk for developing substance use (alcohol and smoking) dependence.